P38γ MAPK contributes to left ventricular remodeling after pathologic stress and disinhibits calpain through phosphorylation of calpastatin. Issue 12 (22nd October 2019) - Loonat, Aminah A.; Martin, E. Denise; Sarafraz‐Shekary, Negin; Tilgner, Katharina; Hertz, Nicholas T.; Levin, Rebecca; Shokat, Kevan M.; Burlingame, Alma L.; Arabacilar, Pelin; Uddin, Shahzan; Thomas, Max; Marber, Michael S.; et al.
Abstract : Despite the high and preferential expression of p38γ MAPK in the myocardium, little is known about its function in the heart. The aim of the current study was to elucidate the physiologic and biochemical roles of p38γ in the heart. Expression and subcellular localization of p38 isoforms was determined in mouse hearts. Comparisons of the cardiac function and structure of wild‐type and p38γ knockout (KO) mice at baseline and after abdominal aortic banding demonstrated that KO mice developed less ventricular hypertrophy and that contractile function is better preserved. To identify potential substrates of p38γ, we generated an analog‐sensitive mutant to affinity tag endogenous myocardial proteins. Among other proteins, this technique identified calpastatin as a direct p38γ substrate. Moreover, phosphorylation of calpastatin by p38γ impaired its ability to inhibit the protease, calpain. We have identified p38γ as an important determinant of the progression of pathologic cardiac hypertrophy after aortic banding in mice. In addition, we have identified calpastatin, among other substrates, as a novel direct target of p38γ that may contribute to the protection observed in p38γKO mice.—Loonat, A. A., Martin, E. D., Sarafraz‐Shekary, N., Tilgner, K., Hertz, N. T., Levin, R., Shokat, K. M., Burlingame, A. L., Arabacilar, P., Uddin, S., Thomas, M., Marber, M. S., Clark, J. E. p38γ MAPK contributes to left ventricular remodeling after pathologic stress and disinhibits calpain through phosphorylation of calpastatin. FASEB J. 33, 13131–13144 (2019). www.fasebj.org